Effect of SLC16A1 on Hepatic Glucose Metabolism in Newborn and Post-Weaned Holstein Bulls - Xue, Mingming; Song, Mingkun; Yan, Duo; Sun, Shuaijie; Wang, Yadong; Fu, Tong; Cai, Hanfang; Xu, Huifen; Sun, Guirong; Wang, Kejun; Li, Ming (Frontiers in Genetics, 2022)
Abstract Background: Patterns of liver energy metabolism significantly differ from birth to adult in cattle undergoing change of rumen rumination. However, the genes involve in hepatic energy metabolism during bovine development and how regulate are still unclear. Methods: In this study, 0-day-old newborn calves (0W) and 9-week-old weaned calves (9W) were used to investigate differences in liver glucose metabolism at these stages of calf development. We did this primarily through the quantitation of energy metabolism indicators, then sequencing the liver transcriptome for each group of claves. Results: The transcriptome results showed 979 differentially expressed genes (DEGs), enriched in animal organ development, catabolic process, transmembrane transport. SLC16A1 involved in that and was locked to investigate. We explored the effects of SLC16A1 on glucose and lactate flux in vitro. We identified and verified its target, miR-22-3p, through bioinformatics and luciferase reporter assays. Moreover, this study found that miR-22-3p decreased cell activity by negatively regulating the SLC16A1. Importantly, our result showed the insulin-induced SLC16A1 mRNA expression decreased, regulated by promoter activity rather than miR-22-3p. Conclusions: Our study illustrates the role of SLC16A1 in the liver mediated metabolism of developing calves. These data enrich our knowledge of the regulatory mechanisms of liver mediated glucose metabolism in developing cattle.